Market Reaction to the January 2026 Trading Halt: Evidence from IDX30 Stocks - Dayan Hakim Natigor NS; Listri Herlina (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to examine the market reaction to the trading halt that occurred on January 29, 2026, on the Indonesia Stock Exchange (IDX), focusing particularly on stocks included in the IDX30 index. Market reactions are analyzed using abnormal returns and trading volume activity. Method: An event study methodology is employed with an eleven-trading-day event window (T?5 to T+5) and a 14-day estimation period, consistent with the standard short-window event study practice in emerging markets, using all 30 IDX30 constituent stocks. Results: Significant abnormal returns were observed only at T?5 (p < 0.05), suggesting partial market anticipation prior to the trading halt. No other days in the event window exhibited significantly abnormal returns, and trading volume activity was insignificant throughout. No statistically significant differences were found between the pre- and post-event periods for either measure. Conclusions: Market response appeared to precede the trading halt rather than follow it, while the halt itself produced no significant change in abnormal returns or trading volume among the IDX30 stocks. Limitations: The findings are based on a single trading halt event and one index, which may limit generalizability across broader market conditions or different halt types. Contributions: This study provides early evidence of the role of trading halt mechanisms in an emerging market context, offering preliminary insights for investors, regulators, and researchers.